Examining Latino Immigrant Caregiver's Self-Efficacy to Support the Prevention of Adolescent Suicide. - Villarreal-Otálora, Tatiana; Gibbs, Jeremy J.; Boyas, Javier F. (Journal of Child & Family Studies, 2023)
As suicide continues to be a leading cause of death for Latino adolescents in the US, their caregivers are strategically positioned to be leaders in its prevention. This exploratory study examined Latino immigrant caregivers' knowledge, engagement, and perceived self-efficacy about Latino adolescent suicide. Participants (N = 133) were first-generation Latino caregivers living in the United States. A multiple regression examined participants' suicide literacy, suicide prevention reinforcement, family and cultural factors, and sociodemographic associations with suicide-related prevention communication self-efficacy (SPCS). Only 23% of participants were familiar with suicide prevention programming. Multiple regression results revealed that suicide prevention reinforcement, familism, and income were significantly associated with the Latino caregiver's SPCS. The findings provide a baseline of Latino immigrant caregivers' SPCS, which can be used to inform providers working with Latino families struggling with suicidality or who have a Latino adolescent at risk for suicide and inform the development of culturally-tailored suicide prevention programming. Highlights: This novel study sought to explore the correlations of suicide prevention communication self-efficacy among Latino immigrant caregivers. Latino immigrant caregivers reported moderately high levels of self-efficacy regarding suicide prevention. Latino immigrant caregiver participants reported low levels of suicide literacy related to suicide warning signs and risk factors. Majority of participants reported a willingness to learn more about preventing adolescent suicide. Familism and hearing about suicide prevention programs were associated with suicide prevention communication self-efficacy.